Environmental Impact of Ghaf Tree (Prosopis cineraria) on Heavy Metals Concentration in Atmosphere - Nizar A. Al Haj Ali; Ideisan Abu-Abdoun; Zohuir A. Albalawna; Khawla A. Al-Shurafa; Nadeen S. Sweisah (International Journal of Minerals, 2024)
The Ghaf is a hardy tree, drought-resistant, and can grow up to ten meters in height, it tree produces small, yellow flowers which attractive to many habitats, like bees, insects, and birds. The leaves and pods of the Ghaf tree have significant antioxidant and anti-inflammatory properties and can be used in new drug development. Ghaf trees can adapt to changing environmental conditions and planting Ghaf trees could be an effective strategy for mitigating climate change in arid regions. The planting and restoration of the Ghaf tree is mostly found in the northern part of the UAE with a unique appearance. In this study, leaf samples were collected from different regions of Sharjah city (UAE), at different distances from traffic roads. The concentration of heavy metals such as; Iron (Fe), Manganese (Mn), Cobalt (Co), Nickel (Ni), Copper (Cu), Zinc (Zn), Chromium (Cr), Cadmium (Cd), Lead (Pb), and Boron (B), in leaves of Ghaf (Prosopis cineraria) tree leaves was measured using Inductively coupled plasma with mass spectroscopy (ICP-MS) various location of Sharjah. The average metal concentrations found in open area locations and far from highways and populated cities in ppm were Fe (381.91), Mn (12.60), Co (0.23), Ni (3.14), Cu (5.45), Zn (8.84), Cr (1.07), Cd (0), Pb (0.94) and B (253.68), and when these metals concentration was measured and compared in crowded locations close to industrial areas the average metals concentration in tree leaves samples was found to be in higher concentrations as follows; Fe (686.30), Mn (27.84), Co (0.53), Ni (5.84), Cu (6.57), Zn (18.89), Cr (3.14), Cd (0.007), Pb (2.06) and B (93.19). This variation in metal concentration in Ghaf tree (Prosopis cineraria) leaves indicates the ability of this tree to intake the pollutants from the atmosphere and thus can work as a pollutant marker besides being an ecological and cultural heritage.
Keywords: Al-Ghaf (Prosopis cineraria) tree; Concentration of heavy metals. Air pollution markers; Prosopis cineraria; United Arab Emirates